Understanding Mathematics’ Classroom Processes What Makes a Class “Innovative”? - Garg, Ruchi (JOURNAL OF INDIAN EDUCATION, 2022)
This paper makes an attempt to study a mathematics class and analyse some of the classroom processes that make the class innovative. The data has been collected from an organisation named ‘Digantar’ in Jaipur. One class of this school was selected and mathematics lessons of this class were observed along with interviewing the teacher. Apparently, innovation is a subjective term and it is difficult to say whether something is innovative or not. However, it was observed that some of the practices made the class completely different in a positive manner for learning mathematics. This included multi-grade and multi-age teaching, providing students the power to decide what and how to learn mathematics, a unique way of giving feedback and most importantly the algorithm teaching. Some of these practices can be used in any class and by any teacher without being in an ‘innovative setting’. The purpose is to make mathematics learning a meaningful activity for students.